Regenerative Endodontic Effectivity In Cases of Necrotic Immature Permanent Teeth Treatment (Literature Review) - M. Rayhan Novriansyah; Merryca Bellinda; Rinda Yulianti; Danica Anastasia; Billy Sujatmiko (Dentistry Study Program, Faculty of Medicine Universitas Sriwijaya, 2024)
Introduction: Pulp necrosis in immature permanent teeth results in incomplete root development with short roots and thin dentinal walls that can lead to fracture. Apexification, the main treatment, did not increase the length and thickness of the root canal wall, making the teeth susceptible to fracture. Regenerative endodontic treatment uses a tissue engineering triad that allows the root to continue developing, increases the dentinal wall thickness, and restores the tooth's vitality to prevent fracture. Purpose: This literature review aimed to examine the effectiveness of regenerative endodontics in treating necrotic immature permanent teeth and which component is the most commonly used and effective. Methods: The literature review uses Google Scholar, DOAJ, Science Direct, and Pubmed data for the last five years, calculated from 2018 to 2023. The journals used fit with the inclusion and exclusion criteria, then analyzed using the Case Report Statement and Checklist and summarized to obtain data on the effectivity of regenerative endodontic treatment in necrotic immature permanent teeth. Results: This literature review successfully synthesized 18 Case Reports from journals that performed endodontic regeneration treatment on immature permanent teeth with necrosis using various components. Conclusion: Regenerative endodontic treatment using NaOCl with concentrations ranging from 1% to 2,5 %, EDTA 17% as irrigation solutions together with Ca(OH)2 as an intracanal medicament and blood clot as a scaffold proven to effectively eliminate disease, induce bone healing, and restoring the vitality of necrotic immature permanent teeth.